Aegle marmelos (L.) Correa from sacred tree to superfruit: A Comprehensive review of its phytochemistry and Therapeutics - Kannan S; Lakshmi Devi; Sanjai R; Ragul Prasanth T.R; Senthilnathan T; Sharmika P; Sivasangari S; Saiyogi Rajan K (International Journal of Pharmacy and Analytical Research, 2026)
Plants are the natural source of food and medicine for both humans and animals, which we have used since the prehistoric era of human civilization. Indigenous plants contain various roles in people's culture and lifestyle. This Review article focuses on the medicinal values and uses of the Indian sacred fruit Aegle marmelos commonly known as Indian Bael fruit.It is an Indian Indigenous plant which is sacred for lord shiva. The nickname of the bael is golden apple which is traditionally used for abdominal disorders, ulcer, cholera, diarrhea, heart diseases, dog bite, jaundice, snake bite etc. Aegel marmelos contains isolated compounds belonging to Alkaloids, Terpenoids, Vitamins, Coumarins, Carbohydrates, Flavonoids, Tannins, Fatty Acids, Essential oils, etc. Hence this review provides concise and standardized information on Aegle marmelos for researchers and students.[8]